Gaining and losing EU Objective 1 funds: Regional development in Britain and the prospect of Brexit - Marco Di Cataldo (London School of Economics and Political Science (LSE), European Institute, 2016)
Leaving the European Union will entail for UK regions losing access to the EU Cohesion Policy. Have EU funds been effective in the country, and what may be the consequences of an interruption of EU financial support to the UK's poorer regions? This paper studies the impact of 'Objective 1' funding – the highest form of EU aid – in Cornwall and South Yorkshire, two of the UK's most subsidised regions. We employ synthetic control, matching and difference-in-differences methodologies in order to assess the labour market and economic performance of the two regions. The results indicate that Cornwall and South Yorkshire performed better than counterfactual comparisons throughout the period in which they were classified as Objective 1. Unlike Cornwall, South Yorkshire lost Objective 1 eligibility in 2006 and this massively reduced its share of EU funds. Our findings indicate that, after 2006, South Yorkshire was unable to sustain the gains obtained in previous years. This suggests that while Structural Funds may be effectively improving socio-economic conditions of poorer regions, the performance of subsidised areas could be deeply affected by a reduction (or worse, an interruption) of EU aid.
Keywords: R11; O18; J60; 330; EU Cohesion Policy; Objective 1; Brexit; synthetic control method; UK